Multifunctional Decorative Plant Shelf Design Concept For Room - Anam, Choirul (Faculty of Civil Engeneering and Planning - ITATS, 2024)
Plants are living things that are nurtured and cared for in a medium. Plants have several benefits, the main one being providing oxygen through photosynthesis. Ornamental plants in this room are used to beautify the house's interior. In addition, seeing some of the benefits of plants that provide oxygen is undoubtedly very influential for health and comfort in the room. However, plants also need sunlight, the most important aspect of their life. Another problem with plants is that they need clear air to launch the photosynthesis process. Therefore, the researcher has a solution: designing a multifunctional ornamental plant rack for the room by adding a diffuser as an air purifier on the plant rack and a sunlight replacement technology that can be used automatically. This study uses mixed methods, a research method combining two methods, namely qualitative methods and quantitative methods, which are used simultaneously. Case studies were conducted in 2 places in the Gresik area and interviewed ornamental plant sellers using needs analysis. This research produces a multifunctional ornamental plant shelf with a minimalist design concept for a room. The minimalist concept uses simple and close elements in technological progress